Exploring and Understanding Differences Between Deliberate and Impulsive Male and Female Burglars - Blevins, Kristie R. (2017)
Relying on rational choice theory, we compare burglars’ varying levels of offense planning to understand differences among types of burglars. Surveys were collected from a sample of incarcerated male and female burglars in three states. Participants answered questions detailing aspects of a burglary including motivations, target selection, deterrents, and techniques. Comparisons were made between 119 deliberate (32%) and 257 impulsive (68%) burglars. Deliberate burglars focused on obtaining cash, whereas impulsive burglars were more motivated by drug habits. Impulsive burglars were more easily dissuaded from a target when multiple obstacles are present. Burglars consider how many obstacles they may have to overcome, providing support for rational choice-based, situational crime prevention efforts. Differences in burglar motivation emerged and are discussed